2023
DOI: 10.2516/stet/2023032
|View full text |Cite
|
Sign up to set email alerts
|

Reactive voltage control strategy of distribution network considering the reliability of photovoltaic power supply

Jifeng Liang,
Tiecheng Li,
Rui Zhang
et al.

Abstract: Photovoltaic power actively regulates the reactive power of the active distribution network, leading to the increase of output current of the photovoltaic inverter. Consequently, the temperature rise significantly impacts the maximum junction temperature of the Insulated Gate Bipolar Transistor (IGBT), leading to fluctuations in the junction temperature. To realize the active support of the reactive power of the photovoltaic power supply and ensure its reliable operation, a reactive voltage control strategy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…As per the flow of the model in Figure 1, it can be observed that the proposed model integrates multiple control devices, including [47],…”
Section: Proposed Design Of An Ensemble Predictive Control Model For ...mentioning
confidence: 99%
“…As per the flow of the model in Figure 1, it can be observed that the proposed model integrates multiple control devices, including [47],…”
Section: Proposed Design Of An Ensemble Predictive Control Model For ...mentioning
confidence: 99%